Sleep Quality And Mental Health Among Junior High School Students - Abelia Putri Kania; Aloysia Ispriantari; Hanim Mufarokhah (PROFESSIONAL HEALTH JOURNAL, 2026)
Introduction: Poor sleep among young people, particularly adolescents, is becoming increasingly common and has adverse effects on mental health, such as stress, anxiety, and depression. This study was conducted to examine how sleep quality relates to the mental health of junior high school students. Methods: This study used a cross-sectional design with total sampling of seventh-grade students at Junior High School PGRI 01 Wagir, Malang Regency. The Pittsburgh Sleep Quality Index (PSQI) was used to measure sleep quality, and the Depression Anxiety Stress Scale-21 (DASS-21) was used to measure mental health. The data obtained were then analysed using Spearman's rank correlation method. Results: A total of 120 respondents participated in this study. This study found that 84 respondents (69.4%) had moderate sleep quality, 31 (25.6%) had good sleep quality, and 5 (4.1%) had poor sleep quality. Regarding mental health status, more than half, 62 respondents (51.7%) were classified normal, 51 respondents (42.5%) were in the moderate category, and only 7 (5.8%) fell into the severe category. Furthermore, there was a significant relationship between sleep quality and mental health in adolescents, with a correlation coefficient of r = 0.647 (p < 0.001). Conclusions: Sleep quality has a significant impact on mental health among junior high school students. Therefore, nurses should design interventions targeting sleep improvement, which should be included in mental health promotion and prevention programs carried out in schools.